High‐resolution dynamically downscaled rainfall and temperature projections for ecological life zones within Puerto Rico and for the U.S. Virgin Islands. (21st September 2020) - Bowden, Jared H.; Terando, Adam J.; Misra, Vasu; Wootten, Adrienne; Bhardwaj, Amit; Boyles, Ryan; Gould, William; Collazo, Jaime A.; Spero, Tanya L.
Abstract: The weather research and forecasting (WRF) model and a combination of the regional spectral model (RSM) and the Japanese Meteorological Agency Non‐Hydrostatic Model (NHM) were used to dynamically downscale selected CMIP5 global climate models to provide 2‐km projections with hourly model output for Puerto Rico and the U.S. Virgin Islands. Two 20‐year time slices were downscaled for historical (1986–2005) and future (2041–2060) periods following RCP8.5. Projected changes to mean and extreme temperature and precipitation were quantified for Holdridge life zones within Puerto Rico and for the U.S. Virgin Islands. The evaluation reveals a persistent cold bias for all islands in the U.S. Caribbean, a dry bias across Puerto Rico, and a wet bias on the windward side of mountains within the U.S. Virgin Islands. Despite these biases, model simulations show a robust drying pattern for all islands that is generally larger for Puerto Rico (25% annual rainfall reduction for some life zones) than the U.S. Virgin Islands (12% island average). The largest precipitation reductions are found during the more convectively active afternoon and evening hours. Within Puerto Rico, the model uncertainty increases for the wetter life zones, especially for precipitation. Across the life zones, both models project unprecedented maximum and minimum temperatures that may exceed 200 days annually above the historical baseline with only small changes to the frequency of extreme rainfall. By contrast, in the U.S. Virgin Islands, there is no consensus on the location of the largest drying relative to the windward and leeward side of the islands. However, the models project the largest increases in maximum temperature on the southern side of St. Croix and in higher elevations of St. Thomas and St. John. Abstract : This study uses several regional climate models to provide high‐resolution, hourly regional climate change projections at 2‐km for Puerto Rico and the U.S. Virgin Islands for mid‐century under the RCP8.5 scenario. Projections are analysed to better understand possible changes to both mean and extreme temperature & precipitation within different ecological life zones within Puerto Rico. These realizations depict robust future drying (dashed line) with largest uncertainty in the amount of drying for the wetter life zones, higher elevations.